2016
DOI: 10.1016/j.stemcr.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β Inhibition Promotes Efficient Myeloid and Lymphoid Hematopoiesis from Non-human Primate-Induced Pluripotent Stem Cells

Abstract: SummaryAdvances in the scalable production of blood cells from induced pluripotent stem cells (iPSCs) open prospects for the clinical translation of de novo generated blood products, and evoke the need for preclinical evaluation of their efficacy, safety, and immunogenicity in large animal models. Due to substantial similarities with humans, the outcomes of cellular therapies in non-human primate (NHP) models can be readily extrapolated to a clinical setting. However, the use of this model is hampered by relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…Notwithstanding their limitations, it is important to continue to use model organisms, which remain virtually unrestricted resources in which to pursue detailed analyses of HSC development. Although not free from ethical and practical considerations, research using nonhuman primates may also provide valuable information that will help to bridge the evolutionary gap between the mouse and human (D'Souza et al, 2016).…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…Notwithstanding their limitations, it is important to continue to use model organisms, which remain virtually unrestricted resources in which to pursue detailed analyses of HSC development. Although not free from ethical and practical considerations, research using nonhuman primates may also provide valuable information that will help to bridge the evolutionary gap between the mouse and human (D'Souza et al, 2016).…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…To ensure a reproducible and robust differentiation approach, we made use of a feeder-free culture system15 in combination with chemically defined differentiation conditions. This is in contrast to reported differentiation methods for NHP pluripotent stem cells, which generally use stem cell culture on feeder cells and differentiation methods based on parameters with high variability, such as embryoid body formation or the addition of serum needed for OP9 co-cultures17262728.…”
Section: Discussionmentioning
confidence: 85%
“…We demonstrate the ability of these lithium-treated ESCs to further derive into HSCs after defined maturation and confirm the endothelialto-hematopoietic transition. Since β-catenin-mediated mechanisms for HSC development are conserved in human and mouse species 5,8,13 our results demonstrate a novel strategy for generating efficiently HSCs in vitro as a multipotent source of stem cells to be used in a variety of blood and muscular biomedical applications.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies have shown that GSK3β inhibition induces HE development from ESCs 5,8 . We next studied whether continued exposure to 2 and 10 mM Li + drives ESC differentiation into HE after 6 days of culture.…”
Section: High Concentrations Of LI + Promote Esc Differentiation Intomentioning
confidence: 95%
See 1 more Smart Citation